STUDI LITERATURE REVIEW GAMBARAN POLA HIDUP SEHAT DALAM MENCEGAH SERANGAN ULANG PADA PASIEN PENYAKIT JANTUNG KORONER - Risma Rahmawati; Nandang Ahmad W; Anah Sasmita; Asep Setiawan (Jurnal Kesehatan Siliwangi, 2020)
This research is backed by the high death each continent due to coronary heart disease (CHD). According to the World Health Agency (WHO) The cause of the most deaths in each continent of all deaths in the world is caused by CHD and 80% of them occur in developing countries. Based on the results of the medical record of the RS Muhammadiyah Gresik in 2016 showed an increase in the rehospitalization patients with complications and re-attacks, one factor of the recurrence of a client with heart attack is due to the inability of coronary heart disease clients in conducting secondary prevention by running a healthy lifestyle. The study aims to determine the healthy lifestyle of life in preventing repeated attacks in coronary heart disease patients using the Systematic Literature Review method by analyzing 3 research results on healthy lifestyles in cardiovascular disease in the range of 2010-2020 years. The results of the analysis showed a healthy lifestyle description of the 3 research results gained, the results of the first research of most respondents (54.6%) Has a good living pattern, and in the second study of 58 respondents obtained 32 respondents (55.2%) Have a good living pattern. Then on the results of the third study as much (76.4%) Of the total respondents have an unhealthy lifestyle. It is hoped that nurses always educate patients to exercise healthy lifestyle according to the recommendation so that there is no re-attack with various health promotion media. Key words : healthy lifestyle, coronary heart disease